Kearifan Tradisional sesudah Upacara Pemakaman â€œPinÉ™danoanâ€ pada Masyarakat Tombatu - Kojong, Maxi (Universitas Sam Ratulangi, 2021)
In society, the behavior of daily life is influenced by the traditions inherited from the ancestors that were carried out long ago. Of the many traditions that are passed down, there are still traditions that still survive or are sustainable or are still being carried out in life. In the Tonsawang tribal community, it is full of traditions. One of the traditions that are still carried out is that after the funeral, there are several traditions that must be carried out by the nuclear family who died. One of the traditions is bathing in the river, washing away the clothes worn. This tradition has been carried out since time immemorial, and is the legacy of the ancestors of the Tonsawang tribe. The purpose of this study is to describe how the traditions are carried out after the funeral. Describe the factors that led to the implementation of the tradition. The last is to describe what the meaning of doing these traditions is. This research uses descriptive analysis.